International Competition Yeongcheon Horse Park in Korea - Grigorieva, Anna (project baikal, 2016)
The international project competition for the design of a Horse Park in Yeongcheon, Korea was organized by the Korean Racing Authority (KRA) and approved by the UIA. The jury awarded three prizes and eight honourable mentions for projects that successfully integrated the themes of horses and nature with the local history and culture.